Modeling, Analysis and Comparative of Down Sampling based Clamping SV PWM for Cascaded and Diode Clamped Multilevel Inverter fed Induction Motor Drive - Ravikumar Bhukya; P. Satish Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper presents investigation and performance analysis of novel down sampling based  clamping SV PWM technique for diode and cascaded Multi-level Invereter fed to Induction motor drive. A novel down sampling based clamping SVPWM has developed by adding triangular off set to sinusoidal fundamental waveform is modified by down sampling the reference wave by order of 10 so this technique is called clamping space vector pulse width modulation techniques such as PD, POD and APOD. so as to shift the lower order harmonics to higher order side. This novel carrier is compared with the offset injected space vector reference waveform to generate the required PWM pulses to the inverter. To analyze the performance of the proposed PWM technique it is implemented on  seven level diode and cascaded Multi-level Inverter using Matlab/Simulink software tool for output line, phase voltage, currents, speed, torque and Total harmonic distortion analysis.